OCEANOGRAPHIC VARIABILITY ANALYSIS USING GIS AND GAM FOR POTENTIAL FISHING ZONE MAPPING OF BIG EYE TUNA (Thunnus obesus) - Semedi, Bambang; ., Hardoko; Agatha, Laily Septiani (JFMR (Journal of Fisheries and Marine Research), 2021)
Southern Waters of Java Island are 573 fisheries management zones, the Big Eye Tuna (Thunnus obesus) commodity is one of fish that has high economic value. There are oceanographic factors affect fish distribution of Big Eye Tuna (Thunnus obesus) such as sea surface temperature, chlorophyll-a, and depth. The data research of Big Eye Tuna fishing zone was obtained from PPSC with data description were year, month, day, number of trips, and number of fish caught around 2018-2019. Oceanographic data used from citra satellite Aqua MODIS for sea surface temperature and chlorophyll-a, and citra satellite ETOPO-1 for depth, by using GAM statistical analysis by looking at the lowest AIC value and the largest CDE value of 7 combined models of oceanographic parameters. The results obtained from statistical analysis using the GAM which was very influential in determining the potential zone for the fishing of Big Eye Tuna (Thunnus obesus) showed that a combination of sea surface temperature + chlorophyll - a + depth with an AIC value of 28840.02 and CDE of 11.1%, with the results Oceanographic parameters optimum sea surface temperature was 25 ° C- 30 ° C, for chlorophyll - a 0.08 - 0.30 mg / m3, and for an average depth of 3500m. The depth parameter had a less positive influence because the Cilacap fishermen used FADs for the fishing area of Big Eye Tuna. The distribution area of Big Eye Tuna (Thunnus obesus) in the Southern of Java Island is at latitude (-7.3 °) - (-14.83 °) and longitude 102 ° - 115.25 °.